Mechanical properties of SiCp/SiC composite lattice core sandwich panels fabricated by 3D printing combined with precursor impregnation and pyrolysis. (15th May 2020) - Zhang, Kun; Zeng, Tao; Xu, Guodong; Cheng, Su; Yu, Siwen
Abstract: Silicon carbide particle/silicon carbide (SiCp /SiC) composite lattice core sandwich panels were fabricated by selective laser sintering (SLS) combined with precursor impregnation and pyrolysis (PIP) process. The compression properties of the SiCp /SiC composite lattice core sandwich panels with three different configurations under room temperature and high temperature were investigated. The room temperature experiment results were compared with the analytical predictions. Experiment results indicated that the compression strength and modulus decreased 34.30% and 44.82% as the temperature increased from 1400 °C to 1800 °C. Moreover, the failure mechanisms of the SiCp /SiC composites were analyzed.